Determining the Best Arch/Garch Model and Comparing JKSE with Stock Index in Developed Countries - Effendi, Kharisya Ayu (Bina Nusantara University, 2015)
The slow movement of Indonesia economic growth in 2014 due to several factors, in internal factors; due to the high interest rates in Indonesia and external factors from the US which will raise the fed rate this year. However, JKSE shows a sharp increase trend from the beginning of 2014 until the second quarter of 2015 although it remains fluctuate but insignificant. The purpose of this research is to determine the best ARCH/ GARCH model in JKSE and stock index in developed countries (FTSE, Nasdaq and STI) and then compare the JKSE with the stock index in developed countries (FTSE, Nasdaq and STI). The results obtained in this study is to determine the best model of ARCH / GARCH, it is obtained that JKSE is GARCH (1,2), while the FTSE obtains GARCH (2,2), NASDAQ produces the best model which is GARCH (1,1) and STI with GARCH (2,1), and the results of the comparison of JKSE with FTSE, NASDAQ and STI are that even though JKSE fluctuates with moderate levels but the trend shown upward trend. This is different with other stock indexes fluctuated highly and tends to have a downward trend.